The Influence of Zinc Supplementation on Improving Learning Concentration and Hemoglobin Levels in Anemic Adolescent Girls at Junior High School - Sahadewa, Sukma; Durry, Fara Disa; Khamidah, Nur; Windayani, Novia Restu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Mild to moderate anemia impairs cognitive performance and academic engagement among adolescent girls, yet school-based nutrition programs in Indonesia focus largely on iron and vitamin A. This study evaluated whether a focused 30-day regimen of 20 mg/day zinc could improve both hemoglobin concentration and attention, as measured by the Stroop Color–Word Test, in 30 junior high school girls with baseline hemoglobin < 12 g/dL. Following daily supplementation, mean hemoglobin rose from 10.6 ± 0.5 g/dL to 12.4 ± 0.4 g/dL (Δ = 1.8 g/dL, p < 0.001, Cohen’s d = 3.86), fully eliminating moderate anemia in this cohort. Stroop scores increased from 61.2 ± 5.3 to 75.8 ± 4.6 points (Δ = 14.6, p < 0.001, Cohen’s d = 2.88), with no students remaining in the lowest concentration category post-intervention. These parallel gains reflect zinc’s dual role in enhancing erythropoiesis improving cerebral oxygen delivery and modulating neurotransmission via NMDA/GABA balance and BDNF upregulation. Effect sizes exceed those typically reported for iron-only or broader micronutrient interventions. Findings support integrating a one-month zinc supplement into Indonesian school-health protocols to rapidly correct anemia and bolster cognitive readiness for learning.